COMPARATIVE STUDY OF ROMANCE AND BETRAYAL IN SHAKESPEARE AND SHAYKHZODA`S LITERARY WORKS. ("OTHELLO" AND "MIRZO ULUGBEK" TRAGEDIES) (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2025)
Abstract. This thesis undertakes a comparative study of romance and betrayal in William Shakespeare's "Othello" and Maksud Shaykhzoda's "Mirzo Ulugbek," exploring how these universal themes are presented and interpreted within distinct cultural and historical contexts."Othello," a quintessential Elizabethan tragedy, depicts the tragic downfall of a Moorish general due to Iago's insidious manipulation and the corrosive power of jealousy. While "Othello" focuses on interracial romance and the societal prejudices it confronts, "Mirzo Ulugbek" likely explores themes of intellectual romance – the pursuit of knowledge and the love for scientific discovery. The thesis will investigate the diverse sources of betrayal in both works. In "Othello," betrayal stems from Iago's malicious ambition and Othello's own insecurities. In "Mirzo Ulugbek," betrayal may arise from political intrigue, religious conservatism, or envy of Mirzo Ulugbek's scientific achievements.